The essential financial toolkit : everything you always wanted to know about finance but were afraid to ask - Estrada, Javier (Libros electrónicos en Ebscohost, 2006)
Math and jargon make essential financial concepts seem intimidating, but that is simply because most books do not have the goal of being accessible to interested readers -- this book does. In ten easy-to-read chapters, it explains all the essential financial tools and concepts, fully illustrated with real-world examples and Excel implementations.